Labor Market Integration of Syrian Refugees in Jordan and Lebanon - Tanissa, Christina (2025)
The Syrian Refugee Crisis is a major humanitarian crisis that has been ongoing for 14 years, and despite recent developments in the country, the critical situation is still present. Syrian refugees are in need to integrate themselves in the labor market of the host countries to gain financial stability and independence. The thesis aims to evaluate the process of integration of the Syrian refugees into the labor markets of two major host countries: Jordan and Lebanon, and to identify the challenges that the refugees have been facing, especially the difficulty in accessing formal employment. The results of the thesis show that Jordan and Lebanon are making efforts to support the refugees; however, the process of integration has many faults and limits refugees from accessing certain job sectors, and pushes them towards the informal economy. This is due to many factors including the difficulty in obtaining a work permit necessary for formal work. Furthermore, a multi-criteria decision analysis was conducted to compare the success of the labor market integration in the two host countries. The concluding outcome showed that Jordan was providing a smoother integration for Syrian workers tied to more structured efforts in comparison with Lebanon.